(3ebOeI aj GdJMdjd GdEbJUGOj GdLRFj (B/s - (3SYjO, YaGa YHO GdLHGQs; (3MSjf, eLjOYdj s ((3YeGf(B: s (3OGQ hGFd(B, s, 2001)
(3WHjYI Yde GdGbJUGO,fXQjI GdWdH,fXQjI GdYQV,fXQjI GdShb,GdfXQjI GdcdGSjcjI aj Sdhc GdeSJgdc,GdfXQjI GdMOjKI aj Sdhc GdeSJgdc,fXQjI GdGfJGL,fXQjI JcGdja GdGfJGL,GdCShGb hJMOjO GdCSYGQ ,CShGb GdefGaSI ZjQ GdcGedI,fXQjI GdJhRjYs
(3HHdjhZQGajG U(B.413 (3cTGa GdeUWdMGJ U(B.401s
Keywords: (3GdGShGbs; (3GdGbJUGO GdLRFjs; (3GdeSJgdcs